2018
DOI: 10.1096/fj.201800965r
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐570 is a novel regulator of cellular senescence and inflammaging

Abstract: Diseases of accelerated aging often occur together (multimorbidity), and their prevalence is increasing, with high societal and health care costs. Chronic obstructive pulmonary disease (COPD) is one such condition, in which one half of patients exhibit ≥4 age-related diseases. Diseases of accelerated aging share common molecular pathways, which lead to the detrimental accumulation of senescent cells. These senescent cells no longer divide but release multiple inflammatory proteins, known as the senescence-asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 56 publications
3
44
0
Order By: Relevance
“…It is unrealistic to achieve reversal of normal aging, but may be more likely to fine tune the pathways that result in premature senescence. However, the reversal of senescence (rejuvenation) in small airway epithelial cells of COPD patients by specific antagomirs suggests that some reversal of senescence might be possible in the future (60,69).…”
Section: Implications For Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…It is unrealistic to achieve reversal of normal aging, but may be more likely to fine tune the pathways that result in premature senescence. However, the reversal of senescence (rejuvenation) in small airway epithelial cells of COPD patients by specific antagomirs suggests that some reversal of senescence might be possible in the future (60,69).…”
Section: Implications For Therapymentioning
confidence: 99%
“…Targeting miRNAs, such as miR-34a and miR-570, may be a future therapeutic strategy for treating and preventing cellular senescence as this has rejuvenates senescent airway epithelial cells in COPD patients (60,69). Delivery of miRNA mimics or antagomirs via extracellular vesicles and nanoparticles might be a novel way to deliver these therapies (90).…”
Section: Targeting Senescence Pathwaysmentioning
confidence: 99%
“…It has been shown that SIRT1 can inhibit cellular senescence of endothelial cells. 38 On the contrary, increased expression and activity of SIRT1 prevent cells from entering into the state of senescence by inhibiting p53 activity.…”
Section: Down-regulation Of Klotho or Sirtuin 1 Expressionmentioning
confidence: 99%
“…37 Furthermore, it has been shown that inhibition of miR-570-3p in small airway epithelial cells from COPD patients restores SIRT1 expression, leading to SIRT1-dependent inhibition of senescence markers and cellular rejuvenation. 38…”
Section: Down-regulation Of Klotho or Sirtuin 1 Expressionmentioning
confidence: 99%
“…MAPK signaling and PI3K signaling were thought to be the possible pathways involved in this response [112,113]. It was reported that SIRT1 was inhibited by p38 MAPK and PI3K signaling via micro-RNA (miRNA) 34-a and miRNA570 expression, if the airway epithelial cells were subjected to oxidative stress [114,115]. The possible mechanisms by which SIRT1 regulates allergic airway inflammation through ILC2, such as cellular apoptosis and lipid metabolic pathways, as well as the presence of miRNAs, require further investigation.…”
Section: The Relationship Between Sirt1 and Ilc2 In Virus-induced Astmentioning
confidence: 99%